The Changjiang River Civilization - Feng, Tianyu. author. aut Link
XV, 257 p. 127 illus., 122 illus. in color.
Keywords: This book is a comprehensive academic introduction of the natural conditions and cultural characteristics of the ChangJiang River Basin. Describing in detail the geographical location and natural conditions of the main stream and the tributaries as the starting point, the book compares the ChangJiang River Civilizations to other civilizations of large rivers of the same latitude. This book reveals the gradual deepening of the Chinese understanding the ChangJiang River, introduces the cultural divisions of the river valley, and describes the evolution of the civilizations in the basin. At the end of the book, the author points out that there are many ecological problems in the ChangJiang River valley, for which the Chinese people have taken many measures, such as water pollution control. Fishing in the main stream and important tributaries of the ChangJiang is banned for at least ten years. As a guide to analyze the natural conditions and cultural characteristics of the whole ChangJiang River Basin, this book enables researchers and common readers to have a relatively clear and comprehensive understanding in a relatively short period of time. Putting the ChangJiang River Civilization in the context of the world’s civilizations, this book makes it easier for readers to understand the uniqueness of the ChangJiang River Civilization and its contribution to the cultural diversity of the world. .